Thai inspired: Thailand through the eyes of Western artists - Konstanz, Dale (Humanities, Arts and Social Sciences Studies, 2023)
Orientalists often focus on Japan and China, and perhaps India and parts of the Middle East, regarding the influence of Asian cultures and Eastern artistic practices on Western art, but few seem to be aware that several prominent artists from the US and Europe have also been inspired by the rich culture of Thailand. Andy Warhol, Robert Rauschenberg, Marina Abramović and her former partner, Ulay, as well as photographers Martin Parr and Andreas Gursky, among others, have traveled to Thailand. The main unifying factor is that during and after their visits each of them produced art that explores concepts related to Thai society, traditions, and beliefs while incorporating a range of classic Thai motifs and other aspects that reference Thai people, as well as Thailand’s natural and built environments into their work. The scope of the paper focuses specifically on Thailand with its distinctive culture, heritage, socio-political history, and aesthetics, albeit it would be worth exploring Western artists’ visits to other parts of Southeast Asia in subsequent articles. Specific artworks created by these artists during or immediately after their visits to Thailand were analyzed to better understand how the culture has been interpreted. The objective is to determine whether these artworks reinforce stereotypes of Thai culture and rely on clichés and common misconceptions. Since the work was created by highly perceptive artists in the late 20th Century and beyond, Thai culture has generally been portrayed with fresh, new perspectives. Yet, since the visits were short-term, theoretically it was not feasible for some of these artists to express a truly deep understanding of Thai culture through their work.